GENETIC ASPECTS OF ATRIAL FIBRILLATION ON THE BACKGROUND OF ARTERIAL HYPERTENSION IN COMBINATION WITH NONCARDIAC DISEASES - L.D. KHIDIROVA; D.A. YAKHONTOV; B.N. MAKSIMOV (Avicenna Tajik State Medical University, 2019)
Objective: To study genetic determinants in patients with atrial fibrillation (AF) on the background of arterial hypertension (AH) in combination with various extracardiac comorbid pathology. Methods: In a prospective cohort study included 167 patients with paroxysmal and persistent forms of AF and stage II hypertension without CAD. The average age of the patients studied was 53.3±7.1 years. DNA isolation from blood leukocytes was carried out by phenol-chloroform extraction. Testing polymorphism rs2200733, polymorphism 174G/C (174G/C (rs1800795) gene IL6), the IL6 gene performed with PCR with RFLP. Testing of statistical hypotheses was carried out at a critical level of significance p=0.05, i.e. the difference was considered statistically significant at p<0.05. The lower limit of the evidential power was taken equal to 80%. Results: This study shows associations of polymorphisms 174G/C (rs1800795) of the IL6 gene, the IL6 gene and rs2200733 chromosome 4q25 with AF on the background of comorbidities: AH, chronic obstructive pulmonary disease, hypothyroidism, T2DM, abdominal obesity. Associations of polymorphism 174G/C (rs1800795) of the IL6 gene with the risk of recurrence of AF on the background of individual comorbidities were also found; polymorphism rs2200733 chromosome 4q25 with triglyceride levels, index atherogenicity, creatinine, fibrinogen, with the number of months before the development of relapse; 174G/C (rs1800795) of the IL6 gene - with HDL cholesterol levels, creatinine, diastolic blood pressure, galectin-3. Conclusion: The results contributes to the study of such a complex phenomenon as the secondary form of atrial fibrillation, contributes to the accumulation of knowledge, bringing closer the time when therapeutic interventions will be individualized, based on an understanding of the pathological process in each patien